Diversity and Taxonomy of Telipogon (Orchidaceae) in Colombia and Adjacent Areas - Szlachetko, Dariusz L. (Monographiae Botanicae, 2022)
The neotropical orchid genus Telipogon Kunth was established in 1815 and currently comprises more than 250 species. Representatives of this genus are generally epiphytic plants lacking pseudobulbs. The stem is either abbreviated or elongate and the leaves are conduplicate. Flowers are usually resupinate with small sepals and petals similar to the lip, but sometimes different. The gynostemium is covered by stiff or soft hairs. This monograph is a presentation of taxonomic diversity of the orchid genus Telipogon in Colombia and adjecent areas. Morphological characteristics of a total of 96 Telipogon species from Colombia are presented together with information about over 50 taxa found in neighboring countries. A brief discussion of an additional seven taxa described in Colombia, but insufficiently characterized, is also given. Illustrations of perianth segments of almost all national genus representatives are provided. Twenty-five species are described in this paper for the first time - Telipogon alinae, T. bicallosus, T. bugalagrandei, T. castanedoi, T. chimborazoensis, T. cocuyensis, T. cuatrecasasii, T. fassetti, T. fernandezii, T. flabellatus, T. garayi, T. hirsutus, T. huertasii, T. idroboi, T. killipi, T. kraenzlinianus, T. orozcoi, T. pasquillensis, T. schlimii, T. spathipetala, T. sumapazensis, T. tolimensis, T. trianae, T. trilabiatus, and T. verrucosus. Several morphologically consistent groups are distinguished to facilitate identification of Telipogon representatives. Keys for determination of species within each group are provided.